Implementation of Somatic, Auditory, Visual and Intellectual (SAVI) Approaches to Improve Student's Mathematics Communication Skills in SMK Negeri 1 Nisam - Abda, Muhammad Ichsan; Muliana, Muliana; Fonna, Mutia (Universitas Malikussaleh, 2020)
The purpose of writing this paper is to study the enhancement of mathematical communication skills of students who have gained the implementation of Somatic, Auditory, Visual, and Intellectual (SAVI) approaches better than those who have learned scientific approaches. The approach used is a quantitative approach with the type of quasi-experimental design with a nonequivalent control group design. The population in this study are all grade X students of SMK Negeri 1 Nisam with a sample of TBSM II class students as an experimental class and TKJ I as a control class taken to use the purposive sampling technique. The data collection techniques used in this research are mathematical communication skills tests of students and observation sheets. Data analysis was done using test-t, that because the data of the n-gain score obtained with normal distribution, but has a variance that is not homogeneous. The significant result of the statistics equal variances not assumed is 0.00 smaller than 0.05 H0 is rejected. The result showed that the enhancement of mathematical communication skills of students who gained the implementation of somatic, auditory, visual, and intellectual (SAVI) were better than students who gained scientific learning approaches.